PENGARUH MODEL KOOPERATIF TIPE THINK TALK WRITE TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK - Ulfah Tri Rusdiarni (Jurnal Edukasi dan Penelitian Matematika, 2020)
This paper discusses the ability of students to understand mathematical concepts that can be improved with the TTW strategy. The low ability of students to understand mathematical concepts is because the learning process is not optimal. Through this research, it is explained theoretically that learning with the TTW strategy can improve students' ability to understand mathematical concepts.This research type is literature study. Data collection is done by searching, collecting and analyzing sources related to topics discussed either from textbooks, journals or other sources.The conclusion from this literature study is that theoretically the ability of students to understand mathematical concepts can be improved by the TTW strategy. This is because at each stage of the TTW it can help students be actively involved and construct their own understanding in increasing understanding of mathematical concepts. Think activity will support students to be able to think independently and be able to construct their own thinking results. During the talk activity, students will gain new understanding from the results of the discussion with their partners. Then, students will give each other good direction and understanding to be able to learn existing concepts. Writing activities will form students who can instill the concepts that are learned from the results of discussions with partners.  Keywords – Ability to understand mathematical concepts, TTW Strategy